PROCEEDINGS OF THE SEMINAR FOR ARABIAN STUDIES VOLUME 49 2019 papers from the fifty-second meeting of the seminar for arabian studies held at the. (ARCHAEOPRESS, 2019)
"The Seminar for Arabian Studies is the principal international academic forum for research on the Arabian Peninsula. First convened in 1968, it is the only annual academic event for the study of the Arabian Peninsula that brings together researchers from all over the world to present and discuss current fieldwork and the latest research. The Seminar covers an extensive range of diverse subjects that include anthropology, archaeology, architecture, art, epigraphy, ethnography, history, language, linguistics, literature, numismatics, theology, and more besides, from the earliest times to the present day or, in the fields of political and social history, to around the end of the Ottoman Empire (1922). The Seminar meets for three days each year, with an ever-increasing number of participants coming from around the globe to attend. In 2018 the fifty-second meeting took place, in which fifty-seven papers and posters were presented in London at the British Museum, where this event has been hosted since 2002"--